Projeto hora da leitura: os sentidos/significados sobre leitura de professores do ensino fundamental II - Nolasco, Sônia Maria (2006)
The results of SARESP (Evaluation System of School Development of São Paulo State) point to a great difficulty of students on reading and text production, which leads to a necessity of changes being made at the school work. Attempting to solve this problem, the S.E.E. implemented the program Reading Time which consists on weekly reading classes for elementary and middle school students. This research, that was conducted with the participation of six reading class teachers and this researcher. It analyzed two reference texts on reading teaching PCN (National Curriculum Parameters) and a reading project Reading Time , focus of this study in order to understand teachers´ meaning to the reading process. This research has also been based on the critical methodology of collaboration in which theoreticalmethodological choices have been directed to interfere on the school context, emphasizing collaboration and critical reflection. Thus, it aims to open space for questioning, analyzing and criticizing social relationships among researcher and participants through reflecting on the role each one plays in the classroom, as well as the interests each one serves. Data has been collected through audio recording of meetings, which have been analyzed by over viewing the general text plan: theme content and enunciate mechanisms (Bronckart, 1997). Results have shown that the meanings of the mentioned texts National Curriculum Parameters and Reading Time present divergences when compared. This has favored the sedimentation of traditional teacher behavior towards reading teaching and the project Reading Time , which, consequently, does not favor the development of proficient readers on the teaching-learning process